2007
DOI: 10.1097/qad.0b013e32825a69d1
|View full text |Cite
|
Sign up to set email alerts
|

Atazanavir plus low-dose ritonavir in pregnancy: pharmacokinetics and placental transfer

Abstract: Atazanavir exposure during the third trimester of pregnancy is similar to that observed in the non-pregnant period. Over the whole dosing interval, therapeutic drug concentrations well above the wild-type HIV 90% inhibitory concentration are maintained. Atazanavir crosses the placenta, potentially providing further protection for the newborn. As pregnancy does not appear to alter atazanavir exposure, no dose adjustment is required in pregnant women. Results suggest that atazanavir is a reasonable component of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 20 publications
5
58
2
1
Order By: Relevance
“…For atazanavir, the ratios were 0.13 (27) to 0.21 (10), and for lopinavir, the ratio was 0.20 (28). Similar ratios were also observed for nelfinavir and amprenavir (29), whereas cord blood concentrations were nearly undetectable for ritonavir, indinavir, and saquinavir (29,30).…”
supporting
confidence: 60%
“…For atazanavir, the ratios were 0.13 (27) to 0.21 (10), and for lopinavir, the ratio was 0.20 (28). Similar ratios were also observed for nelfinavir and amprenavir (29), whereas cord blood concentrations were nearly undetectable for ritonavir, indinavir, and saquinavir (29,30).…”
supporting
confidence: 60%
“…Previous studies have demonstrated placental transfer, with drug concentrations approaching 1 g/ml in maternal and cord blood ratios for certain nucleoside (or nucleotide) reverse transcriptase inhibitors (NRTIs) (15)(16)(17)32) with slightly lower ratios reported for non-NRTIs (18)(19)(20) and even lower ratios for the protease inhibitors (16,21). Studies analyzing placental transfer of TFV have reported variable results, with maternal and cord blood concentration ratios ranging from 0.82 to 6.0 (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…ATV concentrations appear to normalize by week 7 postpartum [18]. The ratio of maternal to cord blood ATV indicates that, as with other protease inhibitors [25], ATV does not freely cross the placenta; however, in this study, plasma protein binding in cord blood was lower than in maternal blood, indicating that free drug concentrations in the fetus were approximately twice as high as in the mothers at a similar total (bound and unbound or 'free') ATV plasma concentration [26], suggesting that the levels achieved in the cord blood may provide some antiviral protection to the fetus [18].…”
Section: Table 2 (Continued)mentioning
confidence: 99%
“…In one study of lopinavir/RTV, compensation for the lower exposures required a dose increase to 533/133 mg twice daily (bid) from 400/100 mg bid in the third trimester to produce exposures similar to those in nonpregnant historical controls [7]. Conversely, Ripamonti et al [18] reported that the standard dose of ATV/r (300/100 mg) resulted in ATV exposures in women in the third trimester that were similar to their postpartum exposures. The most frequently observed adverse event with ATV is elevations of indirect bilirubin as a result of uridine diphosphate glucuronosyl transferase (UGT) 1A1 inhibition, and this gives rise to the theoretical concern that using ATV in pregnant women may exacerbate physiological hyperbilirubinaemia in the neonates [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation